2021
DOI: 10.3390/microorganisms9050905
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation-Based Quantification and Identification of Bacteria at Two Hygienic Key Sides of Domestic Washing Machines

Abstract: Detergent drawer and door seal represent important sites for microbial life in domestic washing machines. Interestingly, quantitative data on the microbial contamination of these sites is scarce. Here, 10 domestic washing machines were swab-sampled for subsequent bacterial cultivation at four different sampling sites: detergent drawer and detergent drawer chamber, as well as the top and bottom part of the rubber door seal. The average bacterial load over all washing machines and sites was 2.1 ± 1.0 × 104 CFU c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Based on the transcript counts, several bacterial genera known to be typical for washing machines and laundered textiles [ 7 , 10 , 13 ] were detected, such as Acinetobacter (48.5%, 51.7%), Aeromonas (26.1%, 21.6%), Rhizobium (6.0%, 6.5%), Agrobacterium (2.9%, 2.4%), Moraxella (1.8%, 2.1%) and Pseudomonas (0.4%, 0.4%) (the brackets show the relative abundances based on the Spades and Trinity assemblies, respectively, averaged over all of the samples). However, we also detected genera which were, to the best of our knowledge, previously not reported as being typical for washing machines or laundered textiles, such as Sphingorhabdus (9.9%, not detected), Anderseniella (2.1%, 12.1%), Epilithonimonas (0.9%, 1.0%), Haematobacter (0.5%, 0.6%) and Escherichia (0.04%, 0.3%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the transcript counts, several bacterial genera known to be typical for washing machines and laundered textiles [ 7 , 10 , 13 ] were detected, such as Acinetobacter (48.5%, 51.7%), Aeromonas (26.1%, 21.6%), Rhizobium (6.0%, 6.5%), Agrobacterium (2.9%, 2.4%), Moraxella (1.8%, 2.1%) and Pseudomonas (0.4%, 0.4%) (the brackets show the relative abundances based on the Spades and Trinity assemblies, respectively, averaged over all of the samples). However, we also detected genera which were, to the best of our knowledge, previously not reported as being typical for washing machines or laundered textiles, such as Sphingorhabdus (9.9%, not detected), Anderseniella (2.1%, 12.1%), Epilithonimonas (0.9%, 1.0%), Haematobacter (0.5%, 0.6%) and Escherichia (0.04%, 0.3%).…”
Section: Resultsmentioning
confidence: 99%
“…Using the molecular approach of 16S rRNA gene pyrosequencing, we recently showed that the relatively most abundant sequence types in domestic washing machines were closely related to potentially pathogenic bacteria, such as Brevundimonas vesicularis or Pseudomonas aeruginosa inside the detergent drawer, and Moraxella osloensis or Acinetobacter parvus inside the door seal [ 7 ]. While this and other structural studies have looked at the microbial community composition of washing machines and laundry items [ 3 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ], studies on the metabolic activities of the laundry microbiota are often limited to distinct functionalities, such as the formation and prevention of malodor [ 2 , 15 , 16 ]. Malodor is often associated with a lack of hygiene, and can negatively affect the life cycle of a textile [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Proteobacteria, Firmicutes, Actinobacteria, and Bacteroidetes were detected in private homes, including Propionibacterium, Bacteroides, and Staphylococcus genera [57]. Staphylococcus and Micrococcus genera were also detected in washing machines, half of which potential opportunistic pathogens, emphasizing the need for effective cleaning and control strategies [58].…”
Section: Pathogen Diversity In the Built Environment Microbiomementioning
confidence: 99%
“…A self-cleaning of the filter is necessary for avoiding the built-up of a bio-film [38]. The sieve is a critical part to clean but the described usage to remove the microfibers together with the sieve solves this drawback.…”
Section: Applicationmentioning
confidence: 99%